The United States Supreme Court and Business Elites: Gilded Age Origins of Modern American Liberalism - Paul Kens (Transatlantica)
One issue that permeated Gilded Age politics asks to what extent the United States Constitution places a limit on government regulation of business. Most of today’s scholars treat it as a matter of balancing economic liberty or property rights against government power, and maintain that this balancing formula represents the predominant tradition in constitutional history, dating at least as far back as the Jacksonian era. On the contrary this paper shows that prior to the late 1880s the paradigm for determining the constitution’s limits on government regulation of business was actually quite different. The Supreme Court in its first century treated business regulation as a matter of balancing entrepreneurial liberty against the rights of the community. Furthermore, it consistently held that, because state economic regulations were an expression of popular sovereignty and rights of the community, they should be presumed to be valid. Only at the very end of the nineteenth century did this interpretation give way to a new one, raising entrepreneurial liberty to preferred status under the Constitution. This was the result of the persistent efforts of lawyers for the corporate elite, who aimed to produced three changes: a tendency to equate regulation of business with confiscation of property; a trend toward expanding the constitutional rights afforded to corporations; and a reversal of the rule that economic regulation should be presumed valid. But at least until the death of Chief Justice Morrison R. Waite in 1888, the Supreme Court would rather steadfastly cling to the traditional doctrine than promote this new interpretation.